Risk of yellow fever virus transmission in the Asia-Pacific region - Lucy de Guilhem de Lataillade (Nature Portfolio, 2020)
Yellow fever is absent from the Asia/Pacific region, despite presence of the mosquito vector. Here, the authors demonstrate that mosquitoes collected from field sites across the region are capable of transmitting yellow fever virus, indicating that vector competence is not a barrier to disease spread.